Computed Tomography Imaging Features of Pulmonary Sequestration - Yang, Yangtian; Wang, Zhaoyu; Qiang, Jun; Mao, Qinxiang; Kong, Shufeng; Sun, Zhonghua; Li, Yu (MDPI, 2023)
Background: Pulmonary sequestration (PS), generally diagnosed using computed tomography pulmonary angiography (CTPA), is a rare congenital developmental malformation of the lung that is characterized by nonfunctional lung tissue, independent of the normal lung tissue. This paper summarizes the imaging features of the supplying arteries and draining vessels in patients with PS with an aim to assist in timely clinical diagnosis and operation guidance. Materials and Methods: A total of 55 patients with PS diagnosed using CTPA from multiple clinical centers were retrospectively analyzed. Data included demographic characteristics, imaging features, disease location, isolation type, and the features of supplying and draining vessels, as shown on CTPA images. Results: Of the 55 patients reviewed, 3 (5.45%) were children, 3 (5.45%) were adolescents, and 49 (89.09%) were adults; the mean age was 44 years. Fifty-four (98.18%) patients had intralobar sequestration and one (1.82%) had extralobar sequestration. PS was noted 3.5 times more frequently in the left lower lobe than in the right lower lobe. For the supplying arteries, 47 (85.45%) were derived from the descending thoracic aorta, 1 (1.82%) from the abdominal aorta, 7 (12.73%) from the celiac axis, and 1 (1.82%) from the bronchial artery. The draining vessels were the pulmonary veins in 49 patients (89.09%), the umbilical vein in 1 (1.82%), the venae intercostal in 1 (1.82%), the pulmonary arteries in 11 (20.00%), and the vessels were not shown on the images in 2 patients (3.64%). Conclusion: Clinical presentations of PS are non-specific and can be easily missed or misdiagnosed. However, CTPA can help to improve the diagnostic accuracy and identify the supplying arteries and draining vessels, which significantly contribute to surgical planning.